Analisis Kebijakan Perkreditan Dan Pengaruh Ldr Terhadap Npl Pada Bank Sinar - yanti, angga novita; baskara, gde kajeng (E-Jurnal Manajemen; Vol 1 No 1 (2012), 2012)
ABSTRACT This study aims to determine the applicable credit policies related to the value of Non-Performing Loans and the effect Loan to Deposit Ratio of Non-Performing Loans in the Bank Sinar. The analysis used is descriptive analysis and simple linear regression. The analysis showed (1) the applicable credit policy Bank Sinar been effective in suppressing the value of Non-Performing Loans below 5 percent. (2) There was a negative and significant correlation between the variables with the loan to deposit ratio of Non Performing Loans. From the calculation of the t-test showed significance level 0.003 is smaller than the value of ? = 0.05, so we can conclude that H 0 is rejected and H a accepted. Keywords: credit policy, LDR, NPL